Third Five Year Plan Volume I Policy and Programme Government of Mysore - Planning Commission (Planning Commission, 1961)
The concept of planned progress understandably exerts a dominant influence over the economic thought and policy of a developing nation. Democratic planning has thus become, like Socialism, an article of our national faith. During the past decade, India has demonstrated through her first two five year plans that this is a way of life which makes rapid economic development possible while preserving individual liberties.
Government of Mysore Planning, Housing & Social Welfare Department
Government of Mysore Planning, Housing & Social Welfare Department